National Intellectual Capital and the Financial Crisis in Argentina, Brazil, Chile, Colombia, Mexico, and Venezuela - Lin, Carol Yeh-Yun.; Edvinsson, Leif.; Chen, Jeffrey; Beding, Tord.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
In the first decade of the twenty-first century, the biggest event of worldwide proportion was the 2008 global financial crisis, which was caused primarily by ineffective governance, failed surveillance systems, and implementation flaws. While fiscal and monetary policies succeeded in pulling many countries out of a financial freefall, most economies have performed beneath pre-recession levels as governments continued to struggle with their finances. Examining the financial crisis from the viewpoint of intangible assets provides a different perspective from traditional economic approaches. National Intellectual Capital (NIC), comprised mainly of human capital, market capital, process capital, renewal capital, and financial capital, is a valuable intangible asset and a key source of national competitive advantage in today$1 (Bs knowledge economy. The authors$1 (Bpioneers in the field$1 (Bpresent extensive data and a rigorous conceptual framework to analyze the connections between the global financial crisis and NIC development. Covering the period from 2005 to 2010 across 48 countries, the authors establish a positive correlation between NIC and GDP per capita and consider the impact of NIC investment for short-term recovery and long-term risk control and strategy formulation. Each volume in a series of SpringerBriefs on NIC and the financial crisis provides in-depth coverage of the impact of the crisis, the aftermath, future prospects, and policy implications for a regional cluster. This volume focuses on Argentina, Brazil, Chile, Columbia, Mexico, and Venezuela.s
Chapter 1 Introduction -- Chapter 2 Impact of the 2008 Global Financial Crisis -- Chapter 3 National Intellectual Capital Development in the Six Latin American Countries -- Chapter 4 Beyond the 2008 Global Financial Crisis -- Chapter 5 Future Perspective and Policy Implication Prospects.
Keywords: Economics; Endogenous growth (Economics).; Economic policy; Regional economics; Economics/Management Science; Economic Growth; Economic Policy; R & D/Technology Policy; Regional/Spatial Science